The Aesthetics of the Upper Face and Brow: Male and Female Differences - Sedgh, Jacob (Facial Plastic Surgery, 2018)
A hallmark of the modern era of facial plastic surgery is the increasing demand for upper facial rejuvenation by both genders and the growing variety of such options, including both surgical and non-surgical modalities. Thus, now more than ever, differentiating these aesthetic ideals between the two genders and understanding their nuances has become a necessity for the facial cosmetics community. In this article, a detailed comparison of the the pertinent anatomical and topographical differences is presented, followed by a review of the historical evolution of these aesthetic trends.
Keywords: male aesthetics; brow aesthetics; female brow; upper face aesthetics